2022
DOI: 10.56369/tsaes.3869
|View full text |Cite
|
Sign up to set email alerts
|

VARIETIES, POULTRY MANURE AND FERTILIZER INFLUENCE ON THE GROWTH AND FIBRE QUALITY OF KENAF (Hibiscus cannabinus L.)

Abstract: <p> </p><p><strong>Background</strong>: The quality of fibre in kenaf is variety and soil fertility dependent. <strong>Objective:</strong> The study was conducted at the Teaching and Research Farm, University of Ilorin, Ilorin, Nigeria, during the 2018 and 2019 cropping seasons to determine the effects of poultry manure and NPK fertilizer on soil properties and fibre quality of four varieties of kenaf <em>(Hibiscus cannabinus</em> L.). <strong>Methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Many studies have shown the positive effects of organic fertilizers, especially cattle manure compost (Adeyeye et al, 2017;Cevheri̇ and Yilmaz, 2018;Eifediyi et al, 2022) and also the positive effect of organic mulch on the growth and yield of shallot (Lasmini et al, 2019), but there is still lack of information about the combination of organic mulch and organic liquid fertilizers on the growth and yield of shallot. Thus, this study aims to evaluate the agronomic performance of the Lembah Palu variety of shallot (A. cepa L. var.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the positive effects of organic fertilizers, especially cattle manure compost (Adeyeye et al, 2017;Cevheri̇ and Yilmaz, 2018;Eifediyi et al, 2022) and also the positive effect of organic mulch on the growth and yield of shallot (Lasmini et al, 2019), but there is still lack of information about the combination of organic mulch and organic liquid fertilizers on the growth and yield of shallot. Thus, this study aims to evaluate the agronomic performance of the Lembah Palu variety of shallot (A. cepa L. var.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque Makinde y Inuwa (2015) indicaron que los guajolotes alimentados con maíz y trigo tienen un crecimiento reducido, sobre todo cuando estos productos suponen más del 15% de la dieta y de acuerdo con Montoya et al (2015), la alimentación a base de concentrados supone entre 60% y 70% del costo final de la carne. Por otra parte, Jerez et al (1994) resaltaron que la producción de guajolote se encuentra estrechamente relacionada con la producción agrícola, como proveedora de granos de cereales como trigo, avena, sorgo y maíz principalmente y Eifediyi et al (2022), destacaron que la cría de aves favorece la producción de estiércol que puede aprovecharse en los cultivos por su alto contenido de carbono orgánico, nitrógeno, fósforo, potasio, calcio y magnesio, para favorecer el rendimiento de granos utilizados en la alimentación de estas especies y otros animales de interés zootécnico. En las condiciones de operación de las UP analizadas, la dieta se complementa con desperdicios de cocina, insectos, gusanos y residuos de la alimentación de otras especies de animales, como lo ha citado INEGI (2020).…”
Section: Discussionunclassified
“…In other words, sawdust is a waste of small particles produced by sawmilling industries, pulp and paper mills, and wood processing. Sawdust biochar can increase soil organic carbon and pH [10], as well as influence plant height, number of leaves, leaf area index, crop growth rate, and yield [11]. However, the research on biochar's potential as a nutrient source for plants is still limited.…”
Section: Introductionmentioning
confidence: 99%